The Effect of Vitamin A Supplementation on Infant Nutritional Status in Sorong City - Mustamir Kamaruddin; Merinta Sada; Nabila Sulfiani; Amelia Damayanti (Jurnal Penelitian Pendidikan IPA, 2025)
Babies will have strong immunity if they get breast milk, because a number of nutrients are transferred from the mother. Breast milk helps protect babies from disease because of the anti-infective substances contained in breast milk and plays an important role in the growth and development of babies. Unfortunately, the target of 80% coverage of breastfeeding in Indonesia is still far from reality. This study aims to determine the effect of high-dose vitamin A supplementation on infant nutritional status. The research design was pre-experimental with a one-group pretest-posttest design conducted from June to September 2024. The statistical analysis used was the Wilcoxon Signed Ranks test with a significance level of 0.05. In this study, the population was all babies at the Remu Health Center, Sorong City. Then, screening of heterogeneous postpartum mothers who had received vitamin A capsules was carried out. Then the heterogeneous study population according to the inclusion criteria with a simple random sampling technique, a homogeneous population was obtained and was willing to fill in the Informed Consent. Two vitamin A capsules were given, namely one capsule on the first day after delivery and one capsule on the second day of delivery. Before being given vitamin A, the baby's weight, height and age were measured. Furthermore, after three months, measurements were taken by measuring BB, PB and Age. Prodia Clinical Laboratory, Sorong Branch for analysis of retinol levels of postpartum mothers. The nutritional status of infants was measured before and after the intervention.